1980
DOI: 10.1002/ar.1091970109
|View full text |Cite
|
Sign up to set email alerts
|

Structure and orientation of extracellular matrix in developing chick optic tectum

Abstract: The mechanisms underlying directed axonal movement in the developing central nervous system are largely unknown. Histochemical methods for transmission and scanning electron microscopy were used to study the surface of the developing optic tectum in the chick embryo at the time of optic fiber ingrowth. A highly structured extracellular matrix consisting of fibrillar and granular components was seen in normal and in uninnervated specimens that had been fixed in solutions containing the cationic dyes Alcian blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…There has been considerable speculation concerning the possible role of glycosaminoglycans as a component of the extracellular matrix in developing nervous tissue (1,4,6,11,14,17,21,22). It is generally agreed that one of the more likely functions of extracellular glycosaminoglycans, particularly hyaluronic acid, is to provide a readily penetrable matrix through which neuronal migration and differentiation may FIGURE 13 Elution of [3SS]sulfate-labeled proteoglycan from adult rat brain (0-----0) and 3H-labeled proteoglycan from 7-d-old brain (O ..... O) from Sepharose CL-2B (0.9 x 65 cm) using 0.2 M sodium acetate buffer, pH 5.6.3ss and 3H counts per minute were normalized as described in the legend to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There has been considerable speculation concerning the possible role of glycosaminoglycans as a component of the extracellular matrix in developing nervous tissue (1,4,6,11,14,17,21,22). It is generally agreed that one of the more likely functions of extracellular glycosaminoglycans, particularly hyaluronic acid, is to provide a readily penetrable matrix through which neuronal migration and differentiation may FIGURE 13 Elution of [3SS]sulfate-labeled proteoglycan from adult rat brain (0-----0) and 3H-labeled proteoglycan from 7-d-old brain (O ..... O) from Sepharose CL-2B (0.9 x 65 cm) using 0.2 M sodium acetate buffer, pH 5.6.3ss and 3H counts per minute were normalized as described in the legend to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, several lines of evidence indicate that matrix components are transiently seen in the developing CNS. First, studies using ruthenium red and other markers of glycosaminoglycans show accumulations of stained, fibrillar, matrixlike material in the extracellular spaces within the developing CNS (Bork et al, 1987;Krayanck, 1980;Nakanishi, 1983). More recently, immunohistochemical studies have revealed the presence of extracellular deposits of laminin, fibronectin, and chondroitin sulfate proteoglycan during brief periods in the brains of embryonic mammals (Aquino et al, 1984b;Chun and Shatz, 1988;Gordon-Weeks et al, 1989;Liesi, 1985b;McLoon et al, 1988;Stewart and Pearlman, 1987).…”
Section: S-laminin Is Produced By Non-neuronal Cells Of the Nervous Smentioning
confidence: 99%
“…Although a matter of controversy for many years, it now seems clear that ECM components are involved in development of the CNS as well (Sanes, 1989;Reichardt and Tomaselli, 199 1). Glycosaminoglycans, defined by labeling with cationic dyes, are present in the cerebral cortex of the mouse (Derer and Nakanishi, 1983;Nakanishi, 1983;Bruckner et al, 1985) and in the chick's optic tectum just ahead of arriving optic nerve axons (Krayanek, 1980). Immunolabeling with antibodies against fibronectin (IN;Hatten et al, 1982;Stewart and Pearlman, 1987;Chun and Shatz, 1988;Stallcup et al, 1989) proteoglycans (Aquino et al, 1984;Margolis and Margolis, 1989;Snow et al, 1990b), hyaluronectin (Delpech and Delpech, 1984;Bignami and Delpech, 1985), laminin (Liesi, 1985;Letoumeau et al, 1988;Liesi and Silver, 1988;McLoon et al, 1988;Hagg et al, 1989), tenascin (Crossin et al, 1989;Steindler et al, 1989), and thrombospondin (O'Shea et al, 1990) has been demonstrated in the developing CNS of the rodent, and extracellular material that has not been characterized with antibody markers is evident with electron microscopy in the cortical subplate and marginal zones (Derer and Nakanishi, 1983;Nakanishi, 1983;Hankin and Silver, 1988).…”
mentioning
confidence: 99%